1996
DOI: 10.1111/j.1365-2621.1996.tb14217.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue/Acidic Phosphate Preblend Effects on Reduced Fat Frankfurters

Abstract: To determine the effect of preblending concentrated sodium acid pyrophosphate (SAPP) with modified beef connective tissue (MCT) on reduced fat frankfurters, samples were target formulated at two fat/added water levels (30/10 and 10/25) and manufactured according to 4 treatments: (1) Control ϭ no phosphate, no MCT; (2) Connective tissue ϭ MCT added alone; (3) Preblend ϭ SAPP, MCT, preblended; (4) Preblend SAPP/MCT ϩ alkaline phosphate. The preblend treatments had the lowest emulsion stability and yields (P Ͻ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
5
1
3
Order By: Relevance
“…Several other researchers found that low‐fat comminuted meats were tougher than those of high‐fat products (Hand and others 1987; Lee and others 1987; Ahmed and others 1990). Calhoun and others (1996) showed that both hardness and cohesiveness of low‐fat (10%) frankfurters were higher than that of high‐fat (30%) products, whereas springiness was lower. Barbut and Mittal (1992) and Gregg and others (1993) also concluded that variations in cohesiveness and springiness were linked to fat content, and springiness of low‐fat sausages was greater than in high‐fat products.…”
Section: Fat Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other researchers found that low‐fat comminuted meats were tougher than those of high‐fat products (Hand and others 1987; Lee and others 1987; Ahmed and others 1990). Calhoun and others (1996) showed that both hardness and cohesiveness of low‐fat (10%) frankfurters were higher than that of high‐fat (30%) products, whereas springiness was lower. Barbut and Mittal (1992) and Gregg and others (1993) also concluded that variations in cohesiveness and springiness were linked to fat content, and springiness of low‐fat sausages was greater than in high‐fat products.…”
Section: Fat Contentmentioning
confidence: 99%
“…Calhoun and others (1996) investigated the effects of adding connective tissue collagen to frankfurters and found that hardness, cohesiveness, chewiness, and springiness all decreased. The previously mentioned findings were further confirmed by Brewer and others (2005) who found gel combinations containing both myofibrillar and gelatin protein were much weaker than either the myofibrillar protein or the gelatin gels alone at similar protein concentrations.…”
Section: Combination Of Myofibrillar and Gelatin Proteinmentioning
confidence: 99%
“…Apesar de não terem sido encontrados dados na literatura abordando a composição química do patê de presunto, alguns pesquisadores têm estudado outros derivados cárneos. Assim, um aumento do teor protéico foi observado, após a incorporação de diferentes proteínas em salsichas, tais como proteínas do germe de milho desengordurado [24], isolado comercial da globina bovina [10] e tecido conjuntivo bovino [4]. Quanto aos minerais no produto final, GUZMÁN et al [9] relataram que em "cooked beef patties" (hambúrgueres pré-cozidos), a adição de um concentrado comercial de células vermelhas de sangue bovino descoloridas provocou uma elevação significativa dos níveis de íons ferro.…”
Section: -Composição Química Dos Patês De Presuntounclassified
“…Em alguns trabalhos realizados com salsichas foram apresentados resultados semelhantes aos obtidos com a GCMC e o CA uma vez que, durante o armazenamento das amostras por 30 a 45 dias, não foram observadas alterações nos valores de pH após a adição de proteínas diversas [4,10,24].…”
Section: -Acompanhamento Por Meio Do Phunclassified
See 1 more Smart Citation